Abandoned Covid-19 personal protective equipment along the Bushehr shores, the Persian Gulf: An emerging source of secondary microplastics in coastlines. (July 2021) - Akhbarizadeh, Razegheh; Dobaradaran, Sina; Nabipour, Iraj; Tangestani, Mahbubeh; Abedi, Delaram; Javanfekr, Fatemeh; Jeddi, Faezeh; Zendehboodi, Atefeh
Abstract: During the Covid-19 pandemic, personal protection equipment (PPE) was widely used to control the virus further spared. In this study, the presence of PPE wastes along the coastline of Bushehr port, the Persian Gulf from nine stations was investigated (4 times during 40 days), and their potential for microplastics (MPs) creation was preliminarily assessed. In total, more than 2380 PPE were collected in the study area. No significant differences were found between various beaches regarding their types and common activities. In addition, the estimated disposal rate of PPE per day and year is 350 and 127, 750 items, respectively. More than 10% of the collected PPE from Bushehr's coastal areas on each sampling day were damaged. Based on the microscopic analysis, the left surgical masks and torn plastic gloves in the coastal regions are emerging sources of secondary microfibers and MP particles (mostly fragments and films) in the marine environments, respectively. Graphical abstract: Unlabelled Image Highlights: The coastal abundance of Covid-19 personal protective equipment (PPE) was investigated. More than 2380 PPE were collected along the Bushehr shores, the Persian Gulf. Blue surgical masks and polyethylene gloves were the most predominant discarded PPE. The disposal rate of PPE items per day and year is 350 and 127, 750 items, respectively. PPE is an emerging source of microplastics in coastal environments.